Blockchain Governance using Reference Architectures - Florez, Luis (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20983, 2022)
Although Blockchain has grown in importance, great barriers still remain, including high failure rates, governance concerns and issues with quality attributes. These barriers have complex interactions and many trade-offs which suggests the need for design tools such as reference governance models and reference architectures. However, these tools are scarce and research in this area, especially governance, is sparse. The object of this research is thus to propose and then validate a new reference governance model and reference architecture to better design systems with desired attributes. The research will be conducted using the design science methodology and validated through case studies.